Paste fill delivery/distribution failures – causes, costs and mitigation/prevention - Horn, A.; Thomas, E.G. (Mine Fill 2014: Proceedings of the Eleventh International Symposium on Mining with Backfill, 2014)
Paste fill formulations focus on use of treated mine/mill waste materials and a variety of additives to reduce the impact/costs of surface waste disposal and improve pertinent underground mining parameters, in the main cost, reserves recovery and local and regional ground stability. Cost of such additives must be optimised.